A novel intumescent flame retardant with nanocellulose as charring agent and its flame retardancy in polyurethane foam. Issue 12 (20th November 2015) - Luo, Fubin; Wu, Kun; Li, Dengfeng; Zheng, Jian; Guo, Huilong; Zhao, Qiang; Lu, Mangeng
Abstract : Ammonium polyphosphate (APP) is microencapsulated with nanocellulose and dicyandiamide‐formaldehyde using in situ polymerization and flocculation method. The presence of nanocellulose and dicyandiamide‐formaldehyde significantly affects the thermal behavior and flame retardancy of microencapsulated ammonium polyphosphate (DFNAPP). DFNAPP is much more stable from 524 to 637°C than that of APP because of the charred formation. Rigid polyurethane foam (PU) composites added DFNAPP obtain higher limiting oxygen index (LOI) values than that with the same loading of APP. Due to the presence of shell, experimental results indicate that DFNAPP obtains better compatibility and water resistance in PU matrix, resulting in the improved mechanical properties of the PU composites and the water durability. LOI value of PU/APP composite added 16.7 wt% additives has a decrement of 3.0% after water treatment. By comparison, that of PU/DFNAPP composite with the same loading of DFNAPP is only 0.3%. Compression strength of PU composite is increased from 195 kPa to 213 kPa when the DFNAPP (16.7 wt%) additive substitutes for APP (16.7 wt%). POLYM. COMPOS., 38:2762–2770, 2017. © 2015 Society of Plastics Engineers